Influences of relative deprivation on health inequality of rural residents in China: A moderated mediation model - Tao, ChunHai; Xu, Jun; Tao, RuoYan; Wang, ZiYu; Li, JiaYi (Frontiers in Psychology, 2022)
With the continuous expansion of income disparity between rural residents, the intensification of health inequality, and the health status of Chinese farmers is not optimistic, analyzing the relationship between individual relative deprivation and rural residents' health inequality is a deepening of the research on the social impact of individual relative deprivation. Using the data of China Family Panel Studies in 2018, taking other residents in the village as the reference group, taking the absolute income hypothesis and relative income hypothesis as the theoretical basis, this paper selects the relative income deprivation and absolute income to comprehensively quantify the generalized impact of farmers' income gap, introduces the psychological capital guidance mechanism, and constructs an intermediary adjustment model for the impact of relative deprivation on the health inequality of rural residents in China from the three dimensions of self-assessment of health, mental health and physical health. The estimation results of the multi-layer model show that the relative income deprivation of rural residents has a significant impact on health inequality, among which the impact of mental health is the strongest. Compared with physical health, the mediated transmission of psychological capital has a more significant impact on the relative deprivation of rural residents and mental health. Compared with low-income groups, high-income residents can better alleviate the reinforcing effect of income relative deprivation on psychological capital poverty and health inequality, and the regulatory effect on physical health is more significant.